THE ASPECTS OF SHARED LEADERSHIP IN HEALTH CARE - Skarbaliene, Aelita; Skarbalius, Egidijus (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Leadership is overwhelming the thinking of contemporary society. A well-functioning organization is first identified with its leader very often. Therefore, it is very important to question the attitude of leadership constantly, not to devalue it, but to understand it better and realize it. Moreover, the expression of leadership in different organizations is very distinct, and its specificity in areas such as health care is still insufficiently explored. Healthcare organizations hold strict hierarchy, therefore leadership is considered as equal to the administrative position. Modern conceptualizations such as transactional, shared, authentic and other leadership theories point to the educational power of a leadership; however, implementation remains challenging. The article presents the analytical-theoretical point of view and interpretive approach for case study about leadership. Firstly, the article introduces research evidence analysis of leadership educational impact for integrated health care system. Secondly, the traditional discourse of leadership is challenged with analysis of complex adaptive systems theory. The case study research was conducted with the purpose to identify the images of leadership among nursing staff and to recognize the needs for leadership education in the healthcare system. Case study results reveal the great need for leadership education in general and for shared leadership in particular.